Transformasi Konsep Khiyār dalam Transaksi E-Commerce: Analisis Maqāṣid al-Sharīʿah terhadap Mediasi Platform Shopee - Al Amin, Zaid (Al-Aqad, 2025)
The expansion of platform-based e-commerce has significantly transformed muʿāmalah transactions, including the operation of khiyār, which in classical fiqh muʿāmalah functions as an individual right to affirm or rescind a contract. In Shopee’s e-commerce transactions, khiyār is no longer exercised personally and flexibly, but is mediated through platform procedures such as escrow mechanisms, fixed complaint periods, and internal dispute resolution. This shift raises normative questions regarding the function and legitimacy of khiyār in contemporary muʿāmalah. This study employs normative legal research using fiqh muʿāmalah and maqāṣid al-sharīʿah approaches, drawing on classical fiqh literature, maqāṣid theory, and Shopee’s transaction policies. The findings show that khiyār has transformed into an institutionalized procedural mechanism. From a maqāṣid perspective, this transformation is functionally acceptable insofar as it protects property and prevents harm, though rigid administrative limits may undermine substantive justice. The study highlights the need to reinterpret khiyār as a maqāṣid-oriented protective instrument adapted to digital transactions.